(untitled) (Journal of Universal Science Research, 2023)
This article is devoted to the analysis of the role of the principle of confidentiality and transparency, which are considered as important features of the international commercial arbitration process, in maintaining the values of arbitration, and the conflicting situations between them. Also, the article examines how confidentiality and transparency are ensured and protected during the arbitration process in the world‘s leading international arbitration centers on the example of arbitration institutions.